The politics of glyphosate regulation: lessons from Sri Lanka's short-lived ban - Tim Dorlach; Sandya Gunasekara (BMC, 2023)
Abstract Background Glyphosate is the world's most used herbicide and a central component of modern industrial agriculture. It has also been linked to a variety of negative health and environmental effects. For instance, the International Agency for Research on Cancer classified glyphosate as "probably carcinogenic to humans" in 2015. This has motivated widespread political demands for stricter glyphosate regulation but so far few governments have followed through. Methods We conduct a case study of Sri Lanka, which in 2015 became the first and so far only country in the world to adopt and implement a complete glyphosate ban. But this ban proved to be short-lived, as it was partially reversed in 2018 (and later fully revoked in 2022). To explain the political causes of Sri Lanka's pioneering glyphosate ban and its subsequent reversal, we employ process tracing methods drawing on publicly available documents. Our analysis is theoretically guided by the multiple streams framework and the concept of self-undermining policy feedback. Results Glyphosate regulation rose to the top of the Sri Lankan political agenda in 2014 when a local scientist linked glyphosate exposure to an epidemic of Chronic Kidney Disease of Unknown Origin (CKDu). A glyphosate ban was eventually adopted in June 2015 by the newly elected government of Maithripala Sirisena. The ban was a political commitment made to the Buddhist monk Rathana Thero and his party, which had supported Sirisena during his presidential campaign. The ban's partial reversal in 2018, implemented through sectoral exceptions, was the result of continued lobbying by export-oriented plantation industries and increased political concerns about potential negative effects on the large and structurally powerful tea sector. The reversal was further aided by the scientific community's failure to corroborate the hypothesized link between glyphosate and CKDu. Conclusions The case of Sri Lanka suggests that strict glyphosate regulation becomes more likely when coupled with locally salient health risks and when decision-making authority is de-delegated from regulatory agencies back to the political executive. Meanwhile, the short-lived nature of the Sri Lankan ban suggests that strict glyphosate regulation faces political sustainability threats, as the apparent lack of cost-effective alternative herbicides motivates persistent business lobbying for regulatory reversal.